Analyzing Cognitive Ergonomics and Key Determinants of Mental Workload in PDPT Operators at Universities - Hakim, Hakim; A.P., Rezki Amelia Aminuddin (JTI: Jurnal Teknik Industri, 2024)
The study commenced by quantitatively measuring the mental workload of Higher Education Operators (PDPT) through the NASA Task Load Index (NASA TLX). Results indicated an even distribution of mental workload between moderate and heavy levels, each comprising 50%. NASA TLX, a standard tool for assessing mental workload, offered insights into the operators' stress levels during task execution. Subsequently, Structural Equation Modeling (SEM) was employed to scrutinize factors impacting mental workload. Independent variables, encompassing completeness of data (CD), Feeder Dikti's time demands (FDTD), Internet network conditions (INC), task complexity (TC), and working period (WP), were tested against the dependent variable, the level of mental workload (LMW). This research provides a holistic understanding of factors contributing to PDPT operators' mental workload and how these factors influence the previously measured workload distribution with NASA TLX. This comprehensive insight adds context to the findings, forming a robust foundation for crafting more targeted management strategies to mitigate and manage mental workload in PDPT environments. Keywords: Mental Workload, NASA TLX, Work Period, PDPT Operator